Distribution Pattern of Pasang Species (Quercus sundaica Blume) in Mount Slamet Forest, East Banyumas Forest Management Unit - Istomo Istomo; Nisa Armila (Jurnal Ilmu Kehutanan, 2023)
Quercus sundaica (Q. sundaica), commonly known as Pasang, is a Fagaceae family member with a significant ecological and economic contribution to Indonesia. This research aimed to examine the abundance, distribution pattern, and physical growth environment of Q. sundaica. The data collection occurred in KRB (Baturraden Botanical Garden) and P7 (Pancuran 7) in the montane and sub-montane zones. The data analysis included vegetation and soil analysis. The KRB track in the montane zone had the highest Importance Value Index (IVI) with a higher density than the KP7 track.